2003
DOI: 10.1046/j.1460-9592.2003.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

End Tidal CO2 Is a Quantitative Measure of Cardiac Arrest

Abstract: Significant changes in ETCO were measured during VF arrest. ETCO can predict acute cardiac arrest in a quantitative manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
0
25
0
1
Order By: Relevance
“…Eleven studies showed that physiological monitoring values (ETCO 2 , coronary perfusion pressure, venous oxygen saturation) increased when ROSC was achieved (LOE 4) [171][172][173][174][175][176][177][178]135,179,180 and that they may be an indication of ROSC before it can be seen in vital signs. 181 Five of the studies found that ETCO 2 was accurate for predicting patients who could not be resuscitated; some gave a time frame for that prediction of 20 minutes (LOE 4).…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies showed that physiological monitoring values (ETCO 2 , coronary perfusion pressure, venous oxygen saturation) increased when ROSC was achieved (LOE 4) [171][172][173][174][175][176][177][178]135,179,180 and that they may be an indication of ROSC before it can be seen in vital signs. 181 Five of the studies found that ETCO 2 was accurate for predicting patients who could not be resuscitated; some gave a time frame for that prediction of 20 minutes (LOE 4).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…176 -178,182,183,886,887 Two prospective human studies demonstrated a significant increase in endtidal CO 2 when ROSC occurs (LOE 5). 140,180 Treatment Recommendation Quantitative measurement of end tidal CO 2 may be a safe and effective noninvasive indicator of cardiac output during CPR and may be an early indicator of ROSC in intubated patients. Although low values of end tidal CO 2 are associated with a low probability of survival, there are insufficient data to support or refute a specific cutoff of end tidal CO 2 at different time intervals as a prognostic indicator of outcome during adult cardiac arrest.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…An abrupt increase in ETCO 2 , under constant ventilation and CO 2 production, provides the fastest indication of ROSC [41][42][43], while ETCO 2 changes may precede a palpable pulse [44,45], which is very important especially when invasive monitoring is not available [46].…”
Section: Return Of Spontaneous Circulationmentioning
confidence: 99%
“…Increases in end-tidal CO 2 typically herald ROSC. 118,119 Additionally, end-tidal CO 2 values greater than 10 mm Hg during CPR are associated with ROSC, 120 whereas values less than 10 mm Hg during CPR are associated with nonsurvival. [121][122][123][124][125][126] End-tidal CO 2 has not been evaluated specifically as a tool to guide resuscitation interventions in real time.…”
Section: Ventilationmentioning
confidence: 99%